KEBIJAKAN PEMBELAJARAN ALQURAN BAGI MAHASISWA PTKI (Deskripsi Pengelolaan Mata Kuliah BTQ Di FAI Unikarta) - Mubarak Mubarak (AZKIYA, 2018)
The Higher Education of Islamic Religious (PTKI) is expected to produce qualified graduates who are scientifically able to make a real contribution to Islam. This expectation is only possible if PTKI becomes a learning organization that makes the Qur'an its scientific base. The Study Programme of Islamic Religious Education (PAI) at the Faculty of Islamic Studies of Kutai Kartanegara University (FAI Unikarta) in its development applied the study of the Qur'an by entering the compulsory course of travel named Read Write Alquran (deacronized become BTQ). The learning result of the Qur'an for the students is able to give significantclues, especially to the students 'ability in reading the Qur'an, as well as the quality of the students' knowledge of the Qur'anic reading law as well as how to write it down. This paper seeks to provide an overview of Quran learning policies for student PTKI on PAI Study Program at FAI Unikarta. The reviews are descriptively used to provide information clearly related to the management of BTQ courses conducted by FAI Unikarta as a model in the application of Koranic learning that is done systematically and programmatically.